Topological excitations and the dynamic structure factor of spin liquids on the kagome lattice - Punk, Matthias; Chowdhury, Debanjan; Sachdev, Subir (Nature physics, 2014)
A quantum spin liquid is a spin state with no magnetic order even at the lowest temperatures. To explain neutron scattering data on a ‘kagome lattice’ antiferromagnet, visons (elementary excitations of vortices) must be included, in addition to the usual fractionalized spinons. Recent neutron scattering experiments on the spin-1/2 kagome lattice antiferromagnet ZnCu 3 (OH) 6 Cl 2 (Herbertsmithite) provide the first evidence of fractionalized excitations in a quantum spin liquid state in two spatial dimensions 1 . In contrast to existing theoretical models of both gapped and gapless spin liquids 2 , 3 , 4 , 5 , 6 , 7 , 8 , which give rise to sharp dispersing features in the dynamic structure factor 9 , 10 , the measured dynamic structure factor reveals an excitation continuum that is remarkably flat as a function of frequency. Here we show that many experimentally observed features can be explained by the presence of topological vison excitations in a Z 2 spin liquid 11 . These visons form flat bands on the kagome lattice, and thus act as a momentum sink for spin-carrying excitations that are probed by neutron scattering. We compute the dynamic structure factor for two different Z 2 spin liquids 2 and find that our results for one of them are in qualitative agreement with the neutron scattering experiments above a very low energy cutoff, below which the structure factor is probably dominated by impurities.